MANAGEMENT FISIOTERAPI PADA PENANGANAN FROZEN SHOULDER SINISTRA DENGAN MENGGUNAKAN TERAPI MANIPULASI DAN MOBILISASI SCAPULA DI RSUD Dr. HARDJONO PONOROGO - Herlambang, Arisandi Fitrilia; Agus Widodo,; Kingkinnarti, Kingkinnarti (Journal of Innovation Research and Knowledge, 2023)
Introduction: Frozen Shoulder Left is glenohumeral joint stiffness caused by non-contractile tissue elements or a combination of non-contractile and contractile tissues that experience fibroplasia. Both passive and active movements are limited and painful. In passive movement, mobility is limited to a capsular pattern with external rotation most limited, followed by abduction and internal rotation. Purpose: This research is to find out the Physiotherapy Management in Handling Left Frozen Shoulder Using Manipulation Therapy and Scapula Mobilization. Methods: Patients are given Scapula Manipulation and Mobilization Therapy. Results: Evaluation was carried out using the Numeric Rating Scale and Manual Muscle Testing. Conclusion: There is a decrease in Numeric Rating Scale pain and an increase in muscle strength with Manual Muscle Testing, so that this intervention is very effective in dealing with Frozen Shoulder Left caused by traumatic injury